Dzień otwarty na Uniwersytecie Przyrodniczo-Humanistycznym w Siedlcach: Open day at the Siedlce University of Natural Sciences and Humanities - Szaniawska, Agnieszka; Bombiak, Edyta (Management and Administration Journal, 2021)
x